The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s11745-006-5008-7
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Step analysis of individual conjugated bile acids in human bile using 1H NMR spectroscopy

Abstract: 1H and 13C NMR spectra of intact human bile were assigned using one-dimensional (1H and 13C) and two-dimensional (1H-1H and 1H-13C) experiments. Individual conjugated bile acids--glycocholic acid, glycodeoxycholic acid, glycochenodeoxycholic acid, taurocholic acid, taurodeoxycholic acid, and taurochenodeoxycholic acid--were identified. The bile acids were quantified accurately and individually in a single step by using distinct and characteristic amide signals. Making use of 13C NMR, the study also suggests a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 25 publications
(31 reference statements)
1
40
0
Order By: Relevance
“…NMR spectroscopy has been previously utilized for the analysis of major biliary biochemicals such as bile salts, phospholipids, and cholesterol [15]. Khan et al [16] have explored the possibility of using 31 P NMR of bile for the detection of pancreaticobiliary malignancies, focusing on the analysis of PC levels.…”
Section: Discussionmentioning
confidence: 99%
“…NMR spectroscopy has been previously utilized for the analysis of major biliary biochemicals such as bile salts, phospholipids, and cholesterol [15]. Khan et al [16] have explored the possibility of using 31 P NMR of bile for the detection of pancreaticobiliary malignancies, focusing on the analysis of PC levels.…”
Section: Discussionmentioning
confidence: 99%
“…While D 2 O served as a field-frequency locking solvent, TSP served as chemical shift as well as a quantitative reference. Recently, from the comprehensive analysis of bile 1 H-NMR spectra, we have shown that the characteristic amide signals constituting three glycine-conjugated bile acids, glycocholic acid (GCA), glycodeoxycholic acid (GDCA), glycochenodeoxycholic acid (GCDCA), and their taurine counterparts, taurocholic acid (TCA), taurodeoxycholic acid (TDCA) and taurochenodeoxycholic acid (TCDCA), invariably appear in the region 7.8–8.1 ppm [20]. We have also shown that these bile acids signals are better distinguished when the coupling between amide protons and the attached methylene protons is removed by decoupling.…”
Section: Methodsmentioning
confidence: 99%
“…It is shown from the experiments performed at different pH that the amide signals of individual conjugated bile acids represent more quantitatively over the pH range 6 ± 0.5 [18, 20]. Hence, the pH of each bile solution was adjusted to this range by the addition of 1–2 μL of 1 N hydrochloric acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the estimation of bile acid in biological fluids has always presented technical difficulty owing to their low concentration and complex structure. Because of the growing interest on bile acid, a number of analytical methods have been developed in the literature for the estimation of bile acid in biological matrices, based on high performance liquid chromatograph (HPLC) with ultraviolet (UV), 9,10 fluorescence, 11 evaporative light scattering 12,13 or electrospray tandem mass spectrometer (MS) detection, 14,15 LC-MS/MS, 16 gas chromatography-mass spectrometry (GC-MS), 17 thin-layer chromatography, 18 nuclear magnetic resonance (NMR), 19 electrochemical sensor, 20-22 chemiluminescence, 23 spectrofluorimetry, 24 ultraviolet-visible spectrophotometry (UV-vis), 25 radioimmunoassay detection and enzymatic-colorimetric method. 26 However, these assay methodologies often suffer from disadvantages of low sensitivity, time consuming, costly reagents and instruments, and complicated pretreatment.…”
Section: Introductionmentioning
confidence: 99%